Chemical profiling of the tuber of Stephania cambodica Gagnep. (Menispermaceae) and analytical control by UHPLC-DAD. Issue 7 (3rd April 2017) - Dary, Chhavarath; Bun, Sok-Siya; Herbette, Gaëtan; Mabrouki, Fathi; Bun, Hot; Kim, Sothea; Jabbour, Florian; Hul, Sovanmoly; Baghdikian, Béatrice; Ollivier, Evelyne
Abstract: A new aporphine glycoside (1 ), named 'angkorwatine', and eight known alkaloids: oblongine (2 ), stepharine (3 ), asimilobine-β-d -glucopyranoside (4 ), isocorydine (5 ), tetrahydropalmatine (THP) (6 ), jatrorrhizine (7 ), palmatine (PAL) (8 ), and roemerine (ROE) (9 ) were simultaneously isolated from the tuber of Stephania cambodica . The development and validation of UHPLC-DAD method was carried out for the quantification of marker compounds (PAL, ROE, THP) of S. cambodica . In addition to good selectivity and linearity ( r 2  > 0.997), trueness, precision, and accuracy of the method did not exceed the acceptance limit of ±10% for ROE, THP and ±20% for PAL. Consequently, this method is able to provide accurate results between 1.39–4.18 μg/mL, 2.01–30.72 μg/mL, and 4.29–64.42 μg/mL for PAL, ROE, and THP, respectively. This study shows that the validated UHPLC method is a rapid, innovative and effective analytical approach to control quality of tubers of S. cambodica and to regulate the usage of this plant in traditional medicine. Abstract :